2018
DOI: 10.3390/app8112230
|View full text |Cite
|
Sign up to set email alerts
|

LDS Realization of High-Q SIW Millimeter Wave Filters with Cyclo-Olefin Polymers

Abstract: In this paper, we present narrow-band substrate integrated waveguide (SIW) millimeter wave band-pass filters, designed using cyclo-olefin polymers (COP). The structures were molded, drilled, and metalized with a laser direct structuring (LDS) process. COP are a type of thermoplastic with low dielectric losses in the millimeter waveband, typically 7.5 × 10−4 at 40 GHz for the COP RS420-LDS from Zeon®. The body of the filter was realized using a molding process that facilitates the combination of thin 50 Ω micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Seewald et al reported in [26] that the partial metallization of trench sidewalls could increase the capacitive coupling and concentrate even more field lines in the air gap, thus minimizing the losses and reducing the width of the transmission line for an LDS-MID structure. Gliese et al reported in [43] an SMD mountable high-Q SIW mmWave filter in LDS-MID technology. Additionally, by replicating the structures from a mold, sequential milling or laser milling processes are no longer required.…”
Section: Discussionmentioning
confidence: 99%
“…Seewald et al reported in [26] that the partial metallization of trench sidewalls could increase the capacitive coupling and concentrate even more field lines in the air gap, thus minimizing the losses and reducing the width of the transmission line for an LDS-MID structure. Gliese et al reported in [43] an SMD mountable high-Q SIW mmWave filter in LDS-MID technology. Additionally, by replicating the structures from a mold, sequential milling or laser milling processes are no longer required.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate integrated waveguide (SIW) technology has been largely employed for the construction of couplers, filters, oscillators, amplifiers, mixers, in addition to antennas since it allows for low-cost implementation, fast prototyping, and precise manufacturing [8][9][10][11][12][13][14][15][16][17][18][19]. It can be used to improve the antenna radiation characteristics, thus obtaining better performances than those of the conventional microstrip/printed board circuits (PCB) while maintaining the typical advantages of planar technologies.…”
Section: Introductionmentioning
confidence: 99%